1997
DOI: 10.1097/00002030-199712000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protease inhibitors on AIDS-defining events and hospitalizations in 10 French AIDS reference centres

Abstract: This study supports the extensive use of HAART in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(108 citation statements)
references
References 2 publications
6
100
0
2
Order By: Relevance
“…[1][2][3][4][5] Unfortunately, virologic rebound commonly occurs in treatmentnaive and treatment-experienced patients.6 -8 Persistent viral replication in the setting of drug selection can lead to the appearance of amino acid substitutions that confer resistance to the current regimen. Thus, identification of patients with acquired drug resistance mutations is critical to achieve virologic suppression and improve patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Unfortunately, virologic rebound commonly occurs in treatmentnaive and treatment-experienced patients.6 -8 Persistent viral replication in the setting of drug selection can lead to the appearance of amino acid substitutions that confer resistance to the current regimen. Thus, identification of patients with acquired drug resistance mutations is critical to achieve virologic suppression and improve patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to what has been reported for NBP in non-HIV-positive immunocompromised patients, the incidence of NBP (and of other infections) has decreased in patients with AIDS receiving HAART in recent in years. In fact, HAART has been shown not only to have a powerful effect on HIV, as shown by the reduction in plasma HIV ribonucleic acid (RNA) and the increase in peripheral T CD4+ cells, but also to reduce the incidence of opportunistic infections (including AIDS-related CNS diseases) and death [12].…”
Section: Discussionmentioning
confidence: 99%
“…In human immunode®ciency virus (HIV)-infected subjects, bacterial pneumonia is responsible for signi®cant morbidity [6±8] and, although most episodes are community-acquired, nosocomial episodes are also not infrequently observed [9±11]. It is also noted that, although the incidence of nosocomial bacterial pneumonia (NBP), as well as other opportunistic infections [12] has decreased considerably in the era of highly active antiretroviral therapy (HAART), NBP still represents an important cause of mortality [13]. However, to the best of the authors9 knowledge, few reports have focused on NBP in such patients.…”
mentioning
confidence: 99%
“…Their theoretical efficacy in reducing the incidence of new AIDS cases and associated mortality, shown in controlled clinical studies [1,2], has since been confirmed in the population [3][4][5][6]. As a consequence, there has been a change in the use of health resources for HIV positive patients from inpatient to outpatient care, and from the use of drugs to treat opportunistic infections to antiviral medications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%